2017
DOI: 10.1097/01.aoa.0000511998.98893.df
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Aspirin Dose on the Prevention of Preeclampsia and Fetal Growth Restriction: Systematic Review and Meta-Analysis

Abstract: (Am J Obstet Gynecol. 2016 pii: S0002-9378(16)30783–30789) Preeclampsia (PE) and fetal growth restriction (FGR) are important causes of perinatal morbidity and mortality. Several studies have suggested that the prophylactic use of low-dose aspirin may help to reduce risk in pregnant women. However, the optimal dosage remains unclear. Therefore, these authors performed a systematic review and meta-analyses of randomized controlled trials and evaluated the dose-response effect of aspirin on the prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 0 publications
1
52
0
5
Order By: Relevance
“…for the prevention of preeclampsia if initiated after 16 weeks gestation (Roberge et al, 2017). A careful and thorough review of personal and family history will identify women who are most at risk for preeclampsia and for whom low-dose aspirin therapy would provide the most benefit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…for the prevention of preeclampsia if initiated after 16 weeks gestation (Roberge et al, 2017). A careful and thorough review of personal and family history will identify women who are most at risk for preeclampsia and for whom low-dose aspirin therapy would provide the most benefit.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have documented that the use of low-dose aspirin among pregnant women at risk for preeclampsia has multiple benefits, including reduced risk of preeclampsia, preterm birth, and IUGR (Henderson, et al, 2014;LeFevre, 2014;Roberge et al, 2017;Rolnik et al, 2017). During clinical trials, researchers have used doses of aspirin ranging from 60 mg to 150 mg; however, there is no consensus on whether any one dose in that range is ideal.…”
Section: Implications For Nursing Practicementioning
confidence: 99%
“…Lowdose aspirin is considered a reasonable preventive strategy and used worldwide for preeclampsia among highrisk groups because of its excellent maternal and fetal safety profile in pregnancy. 3 Several meta analyses showed that lowdose aspirin use in early pregnancy led to significant reductions in the risk of preeclampsia; in one 2017 metaanalysis, 3 aspirin initiated at 16 weeks or earlier reduced the risk of preeclampsia (risk ratio 0•57, 95% CI 0•43-0•75). Additonally, because lowdose aspirin is usually initiated after conception, the use of lowdose aspirin could not be randomised and, thus, might have caused a bias in the results of Hofmeyr and colleagues' study.…”
Section: Prepregnancy Calcium Supplementation and Pre-eclampsiamentioning
confidence: 99%
“…The most effective ASA dose in preventing cardiovascular events seems to be 75-150 mg, which has similar efficacy as doses up to 1500 mg ASA daily (Mansour et al, 2009). A systematic review and meta-analysis of the outcomes moderate and severe preeclampsia and intrauterine growth retardation (Roberge et al, 2016) found that treatment with 75-150 mg ASA daily was associated with a reduction of all three studied outcomes. Individualized dosage of ASA after platelet function testing has been found to be effective in preventing preeclampsia in high-risk women (Rey et al, 2011).…”
Section: Paper IIImentioning
confidence: 99%